2022
DOI: 10.1021/acs.energyfuels.1c03773
|View full text |Cite
|
Sign up to set email alerts
|

PolyE-IL, an Efficient and Recyclable Bronsted Acid Catalyst for Conversion of Rice Straw into Levulinic and Other Organic Acids

Abstract: The lignocellulosic biomass has been identified as a potential renewable feedstock for production of levulinic acid (LA). In the present study, the catalytic thermo liquefaction (CTL) process for liquefaction of rice straw into LA was studied by integrating the polyethyleneimine functionalized acidic ionic liquid (PolyE-IL) catalyst. The screening of various PolyE-IL catalysts with variable counter ions showed the remarkable formation of carbohydrates, LA, formic acid, and acetic acid (AA). Among the tested Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Ukarde et al utilized polyethyleneimine-functionalized acidic ionic liquid catalysts for the conversion of rice straw into organic acids (formic, acetic, and levulinic acids), and it was observed that the catalyst with a [HSO 4 ] − counter ions exhibited superior efficiency compared to other tested catalysts since it has the highest hydrophilicity and Hammett acidity ( Ukarde and Pawar, 2022 ). Moreover, the sodium hydroxide pretreated rice straw was found to provide higher yields of levulinic acid (65.5%) and formic acid (75.8%) than untreated rice straw (levulinic acid: 49.8%; formic acid: 50.5%) ( Ukarde and Pawar, 2022 ). Typically, these organic acids are produced along with the furan derivatives ( Wanninayake et al, 2021 ).…”
Section: Valuable Chemicalsmentioning
confidence: 99%
“…Ukarde et al utilized polyethyleneimine-functionalized acidic ionic liquid catalysts for the conversion of rice straw into organic acids (formic, acetic, and levulinic acids), and it was observed that the catalyst with a [HSO 4 ] − counter ions exhibited superior efficiency compared to other tested catalysts since it has the highest hydrophilicity and Hammett acidity ( Ukarde and Pawar, 2022 ). Moreover, the sodium hydroxide pretreated rice straw was found to provide higher yields of levulinic acid (65.5%) and formic acid (75.8%) than untreated rice straw (levulinic acid: 49.8%; formic acid: 50.5%) ( Ukarde and Pawar, 2022 ). Typically, these organic acids are produced along with the furan derivatives ( Wanninayake et al, 2021 ).…”
Section: Valuable Chemicalsmentioning
confidence: 99%
“…41 The PolyE-IL has serval distinctive properties such as effective solubilization of biomass, ease of separation, and tunable acidity. 42 In our most recent study, the PolyE-IL catalyst was used for CTL of organic biodegradable MSW, and potential indepth reaction pathways were examined. 43 It was observed that the PolyE-IL-catalyzed CTL process could serve as a potential alternative to convert MSW into CTL-Oil as a platform product.…”
Section: Introductionmentioning
confidence: 99%
“…The drawbacks associated with the separation of imidazole-based ILs can be overcome by integrating a polyethyleneimine-based polymeric Brønsted acid IL catalyst (PolyE-IL) . The PolyE-IL has serval distinctive properties such as effective solubilization of biomass, ease of separation, and tunable acidity . In our most recent study, the PolyE-IL catalyst was used for CTL of organic biodegradable MSW, and potential in-depth reaction pathways were examined .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can effectively solubilize and penetrate the cell wall structure of biomass. Moreover, in our previous study use of imidazole-based Bronsted acid ionic liquids catalysts and PolyE-ILs catalyst has been reported for efficient liquefaction of biomass and conversion of rice straw into LA, respectively 37,38. Thus, in the present study [PEI] + [HSO 4 ] − was explored as a catalyst for the catalytic liquefaction of sugarcane bagasse.…”
mentioning
confidence: 96%